Efektifitas Bakteri Pseudomonas Sebagai Pengurai Bahan Organik (Protein,Karbohidrat,Lemak) Pada Media Air Limbah Pembenihan Ikan Lele Dumbo (Clarias sp.) Sistem Resirkulasi Tertutup [Effectiveness Of Pseudomonas Decomposing Organic Matter (Protein, Carbohydrate, Lipid) In Waste Water Of Dumbo Breeding Fish Catfish (Clarias sp.) Closed System Resirculation] - Boedi S. Rahardja; Prayogo Prayogo; Gunanti Mahasri; Mochammad Dwi Hardhianto (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Raising fish rearing African catfish lately more and more attention due to its economical value, easy to maintain and grow quickly. Quality of water at seeding activities have received attention because of seed is a phase that is still vulnerable to environmental changes so that the replacement of water and absolutely must be done if the accumulation of organic materials that cause toxic. African catfish fish hatcheries closed recirculation system based on the work system of water management repeatedly by using a filter (filter) and decomposing bacteria. This study aimed to determine whether the bacterium Pseudomonas pseudomallei index of 97.81% sp, Pseudomonas stutzeri index 61.21% and 97.81% of Pseudomonas stutzeri index may decompose the organic material in an aqueous medium Clarias gariepinus hatchery closed recirculation system and how long required to decompose proteins, lipid and carbohidrat. This research method using descriptive methods, aims to describe symptoms that are based on data collected by observation. Factors include the observation of incubation time at the beginning of the experiment, day 3, day 6 and day-to-9 after incubation performed. This study uses four treatments, namely A (water catfish hatcheries closed recirculation system with the addition of the bacteria Pseudomonas pseudomallei index of 97.81%),B (catfish hatchery water recirculation system closed with the addition of the bacteria Pseudomonas stutzeri index of 97.81%), C (catfish hatchery water recirculation system closed with the addition of the bacteria Pseudomonas stutzeri index of 61.21% and D (catfish hatchery water recirculation system closed with the addition of Pseudomonas pseudomallei index of 97.81%, 97.81% index of Pseudomonas stutzeri and Pseudomonas stutzeri index of 61.21%). Result of this research shows that granting of Pseudomonas pseudomallei sp index 97.81%, 61.21% index of Pseudomonas stutzeri and Pseudomonas stutzeri index decreased 97.81% to give the effect of the proteins, lipid, carbohydrates, BOD and COD. The highest reduce protein content, lipid, carbohydrates, BOD and COD become to combination of pseudomonas bacteria after nine days.